The cost of banking panics in an age before 'too big to fail' - Benjamin Chabot (Federal Reserve Bank of Chicago, 2011)
How costly were the banking panics of the National Banking Era (1861-1913)? I combine two hand-collected data sets - the weekly statements of the New York Clearing House banks and the monthly holding period return of every stock listed on the NYSE - to estimate the cost of banking panics in an era before 'too big to fail'. The bank statements allow me to construct a hypothetical insurance contract which would have allowed investors to insure against sudden deposit withdrawals and the cross-section of stock returns allow us to draw inferences about the marginal utility during panic states. Panics were costly. The cross-section of gilded-age stock returns imply investors would have willingly paid a 14% annual premium above actuarial fair value to insure 100 against unexpected deposit withdrawals The implied consumption of stock investors suggests that the consumption loss associated with National Banking Era bank runs was far more costly than the consumption loss from stock market crashes.
Keywords: 330